Hybrid fuzzy cognitive map modeller: A novel software tool for decision making - Mateou, Nicos; Stylianou, Constantinos; Andreou, Andreas S. (My University, 2005)
This paper presents the key concepts of an integrated software tool designed to contribute to the decision-making process in the field of crisis modelling and management. The tool relies on the use of Fuzzy Cognitive Maps (FCMs), which combine elements of fuzzy logic and neural networks to depict a cognitive scene of interacting concepts (nodes/levels) and their causal relationships (edges/weights). The proposed application provides the policy maker with the ability to input data from various domain experts in the form of activation levels and weight values, and to model the parameters of a certain environment. Simulations may then be performed and their results are presented and analysed for inference purposes and decision-making.
Keywords: Maps; Fuzzy rules; maps FCMs